L’archive traduite : W. S. Merwin troubadour de Hawaii - Françoise Palleau-Papin (Sillages Critiques)
In The Folding Cliffs (1998), his epic poem about the resistance of the Hawaiian island Kaua’i to the deportation of lepers by the colonizers, Merwin translates and adapts into verse a missing or faulty archive, composing a long poem in which the English language sounds estranged from its roots, adopting a local viewpoint. The recreated archive, newly elaborated by an empathetic imagination and following the Western tradition of the troubadours, paradoxically conveys the spirit of Hawaiian resistance in a manner more faithful than the letter of the archives imposed by colonisation.